Analysis of the Impact and Implications of the VAT Rate Increase in Indonesia - Septia Mitha Caesaria; Yusriyah Trinugrahini Mumpuni; Efiearly Mayasha; Galuh Tresna Murti (Publikasi Indonesia, 2024)
This study aims to find out how the impact felt by the community after the implementation of the VAT rate increase policy on individuals who act as end consumers, and business actors or MSMEs who act as distributors. The method used in the study is Systematic Literature Review (SLR) from various studies on the impact and implications of VAT rate increases in Indonesia. The results of the study show that VAT affects the price of goods and services in the market, increases production costs and selling prices, and worsens inflation. However, the increase in VAT rates can also increase government tax revenues, reduce the budget deficit, and stabilize the country's fiscal condition. In addition, the increase in VAT can affect consumer behavior and business investment, especially in the manufacturing, trade, and service industry sectors.